CHALLENGES AND OPPORTUNITIES OF ONLINE ASSESSMENT IN SECONDARY SCHOOLS - Aralova Madina Baxtiyor qizi (Bright Mind Publishing, 2025)
This article explores the dual nature of online assessment in secondary schools, focusing on both its promising benefits and significant challenges. While digital tools offer flexible, engaging, and data-driven testing environments, they also raise concerns about access, equity, and academic integrity. Based on recent literature and personal observation during practical experience in secondary school settings, the study highlights how schools can balance innovation with inclusion and accountability.
Keywords: online assessment, secondary schools, challenges, opportunities, digital education